Nanoantagonists with nanophase-segregated surfaces for improved cancer immunotherapy. (February 2018) - Ma, Yang; Qiao, Sheng-Lin; Wang, Yi; Lin, Yao-Xin; An, Hong-Wei; Wu, Xiao-Chun; Wang, Lei; Wang, Hao
Abstract: The blockade of PD-1/PD-L1 interaction by peptide antagonists can unleash and enhance pre-existing anti-cancer immune responses of T cells to eradicate cancer cells. However, low proteolytic stability is the "Achilles' Heel" of peptides. Here, we first report a nanoantagonist with a physiological temperature sensitive nanophase-segregated surface that exhibits significantly enhanced blood circulation, peptide stability and PD-L1 immune checkpoint blockade efficacy. Thermosensitive polymers with different phase transition temperatures (Tt) are used to form the nanophase-segregated surface on an Au nanorod core. Importantly, the nanophase-segregated surface aids the nanoantagonist to resist protein adsorption and enhance the systemic stability of the linked peptides. Finally, the as-designed nanoantagonist effectively blocks PD-1/PD-L1 interaction in vitro and in vivo, enhances the pre-existing CD8 + T cell tumor destruction capability and inhibits tumor growth. This study offers a new strategy for designing nano-formulations for cancer immunotherapy.